Physical research of microgravity influence on physical phenomenon in cryogenic liquids and general-purpose onboard cryogenic facility for realization of this researchaboard International Space Station - Bondarenko1, S.I.; Deev, V.I.; Kutsenko, K.V.; Kharitonov, V.S.; Zhukov, V.M.; Selyaninova, Yu.Yu.; Korolyov, P.V.; Kryukov, A.P.; Dergunov, I.M.; Shcherbakova, N.S.; Rusanov, K.V.; Eremenko, V.V.; et al. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The united research plan named "Boiling" is created on the basis of several cryogenic research projects developed by experts in Russia and Ukraine for International Space Station. The "Boiling" plan includes 8 first experiments aimed at investigating the influence of microgravity on boiling processes, heat transfer and hydrodynamics in liquid helium being either under normal or superfluid conditions. The experiments are supposed to be carried out with individual cells collected inside a single cryogenic onboard experimental facility. The international research program experiments are characterized by the following features: utilization of several artificially simulated microgravity levels, owing to rotation of the experimental helium cryostat; visualization of the processes that occur in liquid helium; research of boiling and hydrodynamics both in a large volume of stationary liquid, and in a liquid flow running through a channel. Upon completion of the "Boiling" research plan, the cryogenic onboard facility created for International Space Station would be able to find its application in further scientific and experimental researches with helium.